(untitled) (Revista BOEM, 2025)
Considering the challenges faced by mathematics teachers in terms of classroom approaches, this project was conceived with the objective of establishing or reinforcing a logical foundation for the teaching of plane geometry. The proposal seeks to relate simple, everyday forms to the geometric objects studied in the classroom. It was observed that many students fail to recognize the importance of mathematics education, as they are unable to connect the content addressed in class with their social reality. Based on the studies of Marco Antônio Moreira (2006) on meaningful learning, and the theoretical concepts proposed by David Paul Ausubel (1965), the activity “What’s in the Box?” was implemented — a technological learning game that exemplifies the main concepts defended by Ausubel: subsumers, cognitive structure, advance organizers, and anchoring. In line with the proposal of the Learning Psychology course, part of the curriculum of the Full Degree in Mathematics at the Federal Institute of Education, Science and Technology of Pará (IFPA), Belém campus, this dynamic is presented as an educational resource and pedagogical support tool for teaching mathematics.